2006
DOI: 10.1186/1897-4287-4-1-39
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Amplification Has no Prognostic Value in Sporadic and Hereditary Ovarian Tumours

Abstract: Whereas HER2 amplification is a well-known phenomenon in breast tumours, its frequency and clinical importance in ovarian cancer have not been established. The aim of the study was to compare the frequency of HER2 amplification in hereditary (BRCA-positive) and sporadic (BRCA-negative) ovarian tumours and to estimate the association of this gene alteration on clinical outcome in ovarian cancer patients. We analysed HER2 amplification in 53 ovarian tumours: 20 from mutation carriers (18 in BRCA1 and 2 in BRCA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Interestingly, a comparative analysis of the frequency of HER-2/neu amplification and protein expression conducted by El-Gerzawy et al didn't reveal any differences between patients with familial vs sporadic breast cancer by these parameters [33]. In addition, no such dependence was found among patients with hereditary (in BRCA1/2 mutation carriers) and sporadic ovarian cancer [34]. However, in a study by Chappuis et al a significant increase in expression of cyclin E1 was reported in breast cancer patients with hereditary mutations in the BRCA1 gene [35].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, a comparative analysis of the frequency of HER-2/neu amplification and protein expression conducted by El-Gerzawy et al didn't reveal any differences between patients with familial vs sporadic breast cancer by these parameters [33]. In addition, no such dependence was found among patients with hereditary (in BRCA1/2 mutation carriers) and sporadic ovarian cancer [34]. However, in a study by Chappuis et al a significant increase in expression of cyclin E1 was reported in breast cancer patients with hereditary mutations in the BRCA1 gene [35].…”
Section: Discussionmentioning
confidence: 95%